Pengembangan Media Pembelajaran Interaktif Berbasis Metakognitif untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis pada Materi Statistika - Intan Permatasari; Andika Setyo Budi Lestari; Keto Susanto (Lembaga Yasin AlSys, 2026)
Observations at SMP Negeri 2 Pasuruan showed that students continued to experience difficulties in solving mathematical problem-solving tasks in statistics. This condition was influenced by the use of learning media that were insufficiently interactive and unable to optimally facilitate metacognitive activities, while the development of metacognition-based interactive learning media at the junior high school level remains limited. This study aims to develop valid, practical, and effective metacognition-based interactive learning media to improve students’ mathematical problem-solving abilities. The study employed a research and development method using the 4D model, which comprises the define, design, develop, and disseminate stages. The study involved 31 Grade VIII-B students at SMP Negeri 2 Pasuruan who were selected through purposive sampling based on the subject teacher’s considerations. Data were collected through observation, documentation, expert validation sheets, teacher and student response questionnaires, and a mathematical problem-solving ability test. The data were analyzed using descriptive percentage analysis, a paired-samples t-test, and normalized gain. The findings showed that the developed learning media met the criteria for being highly valid, practical, and effective in improving students’ mathematical problem-solving abilities. These findings affirm that integrating metacognitive activities into interactive learning media can support more active and reflective mathematics learning and contribute to improving mathematical problem-solving abilities. This study may also serve as a reference for developing metacognition-based learning media across broader subject matter, educational levels, and sample sizes.